2016
DOI: 10.1155/2016/9582793
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Diabetic Ketoacidosis in Children with Newly Diagnosed Type 1 Diabetes

Abstract: Aim. The aim of this study was to evaluate the incidence of diabetic ketoacidosis in children and adolescents with newly diagnosed type 1 diabetes in 2006-2007 and 2013-2014. Method. The study group consisted of 426 children aged 0–18 years with type 1 diabetes onset admitted to our hospital in 2006-2007 (group A) and 2013-2014 (group B). The study comprised the analysis of medical and laboratory records from patients' medical charts and the electronic database. Results. There was no difference between groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
21
3
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 23 publications
7
21
3
9
Order By: Relevance
“…This discrepancy might be due to methodological differences, in those two studies the incidence was calculated based on newly diagnosed DM, but in the current study, the incidence was estimated based on known diabetes diagnosed children. This nding is much higher than studies done in the US which was 25.5% [22] , 40.3% in Italy [23] , 27% in New Zealand [24] in Poland 28% [25] , 40% in southern Iraq [26] . This discrepancy might be due to methodological differences, in the US the incidence was calculated based on newly diagnosed DM, in others the incidence was calculated based on both newly diagnosed DM and known diabetes children but in the current study, the incidence was estimated based on known Diabetes.…”
Section: Predictor Of Diabetic Ketoacidosiscontrasting
confidence: 59%
“…This discrepancy might be due to methodological differences, in those two studies the incidence was calculated based on newly diagnosed DM, but in the current study, the incidence was estimated based on known diabetes diagnosed children. This nding is much higher than studies done in the US which was 25.5% [22] , 40.3% in Italy [23] , 27% in New Zealand [24] in Poland 28% [25] , 40% in southern Iraq [26] . This discrepancy might be due to methodological differences, in the US the incidence was calculated based on newly diagnosed DM, in others the incidence was calculated based on both newly diagnosed DM and known diabetes children but in the current study, the incidence was estimated based on known Diabetes.…”
Section: Predictor Of Diabetic Ketoacidosiscontrasting
confidence: 59%
“…Studies with larger samples may help to clarify this issue. Ketoacidosis generally occurs in children aged <5 years with type I diabetes and low levels of effective insulin action (29,33). In the present study, no evidence of this condition was indicated, even in patients who received no insulin therapy.…”
Section: Discussionmentioning
confidence: 45%
“…However, this nding is much higher than studies done in the US which was 25.5% [21], 40.3% in Italy [22], 27% in New Zealand [23], 28% in Poland [24], 40% in southern Iraq [25]. This discrepancy might be due to differences in methodology, lifestyle, culture, economical status, access to health care facilities, and level of education of the general public.…”
Section: Discussionmentioning
confidence: 64%